"Quasi‐freestanding" Graphene‐on‐Single Walled Carbon Nanotube Electrode for Applications in Organic Light‐emitting Diode. Issue 5 (29th October 2013) - Liu, Yanpeng; Jung, Eun; Wang, Yu; Zheng, Yi; Park, Eun Ji; Cho, Sung Min; Loh, Kian Ping
<x xml:space="preserve">Abstract</x> An air‐stable transparent conductive film with "quasi‐freestanding" graphene supported on horizontal single walled carbon nanotubes (SWCNTs) arrays is fabricated. The sheet resistance of graphene films stacked via layer‐by‐layer transfer (LBL) on quartz, and modified by 1‐Pyrenebutyric acid N‐hydroxysuccinimide ester (PBASE), is reduced from 273 Ω/sq to about 76 Ω/sq. The electrical properties are stable to heat treatment (up to 200 ºC) and ambient exposure. Organic light‐emitting diodes (OLEDs) constructed of this carbon anode (T ≈ 89.13% at 550 nm) exhibit ≈88% power efficiency of OLEDs fabricated on an ITO anode (low turn on voltage ≈3.1 eV, high luminance up to ≈29 490 cd/m2, current efficiency ≈14.7 cd/A). Most importantly, the entire graphene‐on‐SWCNT hybrid electrodes can be transferred onto plastic (PET) forming a highly‐flexible OLED device, which continues to function without degradation in performance at bending angles >60°.